Effects of Using Pesticide Mixer with Farmers’ Blood Cholinesterase Levels in Na Mai Subdistrict, Lat Lum Kaeo District, Pathum Thani Province - Wongsakoonkan, Watcharaporn; Ju-ngam, Busaya; Outama, Amata; Nunbhakdi, Khwankhae (Health Science Journal of Thailand, 2025)
This research aimed to study the effect of pesticide mixer use on the levels of the blood cholinesterase enzyme levels of farmers in Na Mai Subdistrict, Lat Lum Kaeo District, Pathum Thani Province, from a sample of 200 people. The study was divided into 4 phases as follows: 1) Study the problem of exposure to pesticides; 2) Study the need for problem solving in working with pesticides; 3) Design and develop pesticide mixers; 4) Experiment and evaluate. Data were collected using a questionnaire, group discussion guidelines, and reactive paper. Data were analyzed using descriptive statistics and the McNemar test. The design result of the pesticide mixer includes a mixing tank, cover, motor, mixing shaft, impeller, solar panel set, switch, and on-off valve. Before the experiment, the sample group had normal levels of blood cholinesterase enzyme levels (8.50%) and moderately risky behaviors when working with pesticides (80.50%). After the experiment, the risk behavior scores of working with pesticides were significantly decreased (p-value < 0.001), and the farmers' cholinesterase levels in the blood were significantly increased to a normal level (47.5%) (p-value < 0.001). The study's findings suggest that the pesticide chemical mixer can be used as a pilot tool in agriculture to reduce farmers' pesticide exposure.